Cranial ontogeny of the sole, dagetichthys marginatus (soleidae), with considerations on the feeding ability of larvae and early juveniles - Ende, Stephan Siegfried Werner (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2008)
The overall aim of this study was to gain a better understanding of the feeding mechanisms of the larvae and early juveniles of the sole, Dagetichthys marginatus (Soleidae), with which to assess the suitability of current feeding protocols and to facilitate the development of an appropriate pelleted feed. This was achieved by examining the ontogeny of the cranium of laboratory reared sole, with particular emphasis on those elements associated with feeding and by comparing the cranium of juvenile fish with that of adult fish. At 4 dah (days after hatch) Dagetichthys marginatus larvae develop the first rudimentary branchial arches that facilitates the capture and ingestion of food items. Subsequent development of cranial structures, such as the oral jaws, suspensorium, neurocranium, hyoid and branchial arches and the opercular apparatus enables the larvae, at 16 dah, to switch from ram feeding to suction feeding on live prey. The use of live Artemia nauplii from 4 to 16 dah is therefore appropriate. The first morphological asymmetries developed at 16 dah in the dentaries and at 22 dah the maxillae and the premaxillae began to show asymmetries. Teeth were present only on the blind side of the oral jaw elements and during this period (16 to 22 dah) the existing elements began to ossify. From 16 to 35 dah the standard feeding protocol consists of a combination of pelagic (Artemia metanauplii) and benthic prey (dead, frozen Artemia nauplii) and from 25 dah onwards a sinking pellet is provided. The time (dah) at which frozen Artemia and sinking pellets were provided, appropriately corresponded to the initiation of benthic feeding behaviour. However at this stage the use of pelagic Artemia metanauplii is inappropriate and unnecessary. At 31 dah the cranial morphology resembled that of adult fish. Adult D. marginatus display extreme asymmetries among the elements of the oral jaws, the suspensorium and certain elements of the neurocranium. Elements on the blind side are larger and more robust than those on the ocular side and are adapted for feeding, while those on the ocular side appear to have a respiratory function. From 31 dah the cranial elements are identical to those of adult fish, suggesting that no further feeding behavioural changes occurred and that a sinking pellet, of which the nutrient composition meets the requirements of the fish, would be appropriate for ongrowing.
Keywords: Soleidae; Fishes -- Larvae -- Food; Flatfishes -- Nutrition; Artemia